2016
DOI: 10.1186/s13071-016-1899-1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pvama1 genes from China-Myanmar border reveals little regional genetic differentiation of Plasmodium vivax populations

Abstract: BackgroundWith the premise of diminishing parasite genetic diversity following the reduction of malaria incidence, the analysis of polymorphic antigenic markers may provide important information about the impact of malaria control on local parasite populations. Here we evaluated the genetic diversity of Plasmodium vivax apical membrane antigen 1 (Pvama1) gene in a parasite population from the China-Myanmar border and compared it with global P. vivax populations.MethodsWe performed evolutionary analysis to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 69 publications
(102 reference statements)
6
17
2
Order By: Relevance
“…One of the possible reason for higher immunogenicity for PvMSP-1 19 could be its conserved genetic nature, which were reported in many studies [21, 4247] and the similar observation were recorded in our field isolates collected from Chennai, Nadiad and Rourkela (unpublished data). In contrast, Pvama - 1 gene found to be highly polymorphic at these three study sites (unpublished data) and also in various previous studies [4854]. Another possible reason could be higher exposure of PvMSP-1 19 on the surface of infected RBCs until the end of the intracellular cycle [27].…”
Section: Discussionsupporting
confidence: 58%
“…One of the possible reason for higher immunogenicity for PvMSP-1 19 could be its conserved genetic nature, which were reported in many studies [21, 4247] and the similar observation were recorded in our field isolates collected from Chennai, Nadiad and Rourkela (unpublished data). In contrast, Pvama - 1 gene found to be highly polymorphic at these three study sites (unpublished data) and also in various previous studies [4854]. Another possible reason could be higher exposure of PvMSP-1 19 on the surface of infected RBCs until the end of the intracellular cycle [27].…”
Section: Discussionsupporting
confidence: 58%
“…Numbered black residues: amino acids with possible influences for DmelOrco VUAA-binding and sensitivity [cysteines, Turner et al 37 ; aspartates 357 and 466 36 , the respective position on DmelOrco related to the B. mori tyrosine 464 38 , for which mutagenization alters current–voltage relationships, and Potassium selectivity (tyrosine 478), and their respective positions on CpomOrco (right)]. Yellow residues: Calmodulin binding sites (“SAIKYWVER” 50 ). Red residues: ICL-3 histidine (left) and the respective substitution on CpomOrco (Q, right).…”
Section: Resultsmentioning
confidence: 99%
“…This observation was further reinforced by the very low F ST value obtained among these GMS populations (F ST = 0.025-0.085). Studies on vaccine candidate genes such as PvAMA1 genes also showed high diversity and little differentiation of the P. vivax parasites from China-Myanmar border [67]. Nevertheless, parasite populations from the GMS did fall into several distinctive clades, suggesting the presence of gene flow barriers or/and divergent selection on the Pvmdr1 protein.…”
Section: Discussionmentioning
confidence: 99%